A person and bioethics. What is the conception of man and human lifetime in bioethics? - Kowalski, Edmund (Studia Ecologiae et Bioethicae, 2004)
The present article proposes an approach to bioethical reflection in terms of reading and interpretation of personalist philosophy. Therefore particular attention is given to the theoretical perspectives and practical indications that are relative to human life, the human body, and the person understood as a process in the ever-open task of achievement and development: therefore, from an ethical perspective. Through a direct reading of the texts of G. Marcel and E. Mounier, as well as the critical literature relevant to them, the author has posed the question of indicating the perspectives and dynamics which are a concrete part of the project of the French personalists in the elaboration and construction of a new humanism through the process of personalization of the human being and his/her world (cultural ethics).